Bioremediation and CO2 scavenging using molybdenum-containing enzymes - Fonseca, Luís Filipe Madureira (2014)
Carbon dioxide valorization, will not only help to relieve the greenhouse effect but might also allow us to transform it in value-added chemicals that will help overcoming the energy crisis. To accomplish this goal, more research that focus on sequestering CO2 and endeavors through a carbon-neutral or carbon-negative strategy is needed in order to handle with the dwindling fossil fuel supplies and their environmental impact. Formate dehydrogenases are a promising means of turning CO2 into a biofuel that will allow for a reduction of greenhouse gas emissions and for a significant change to the economic paramount. The main objective of this work was to assess whether a NAD+-independent molybdenum-containing formate dehydrogenase is able to catalyze the reduction of CO2 to formate. To achieve this, a molybdenum-containing formate dehydrogenase was isolated from the sulfate reducing bacteria Desulfovibrio desulfuricans ATCC 27774. Growth conditions were found that allowed for a greater cellular mass recovery and formate dehydrogenase expression. After growth trials, kinetic assays for formate oxidation and CO2 reduction were performed and kinetic parameters determined. For the formate oxidation reaction, a KM of 49 μM and a turnover constant of 146 s-1 were determined. These kinetic parameters are in agreement with those determined by Mota, et al. (2011). Finally, we found that this molybdenum-containing enzyme was able to catalyze the reduction of CO2 to formate with a turnover constant of 4.6 s-1 and a KM of 13 μM. For the first time a NAD+-independent molybdenum-containing formate dehydrogenase was found to catalyze CO2 reduction, allowing its use as a biocatalyst in energetically efficient CO2 fixation processes that can be directed towards bioremediation or as an alternative and renewable energy source. Characterizing these enzymes may lead to the development of more efficient synthetic catalysts, make them readily available and more suited for practical applications.